Site‐Selective N‐Methylation of 5, 15‐Diazaporphyrins: Reactive Cationic Porphyrinoids that Provide Isoporphyrin Analogues. Issue 12 (6th February 2020) - Chia, Wen Xi; Nishijo, Mayu; Kang, Seongsoo; Oh, Juwon; Nishimura, Tsubasa; Omori, Hiroto; Longevial, Jean‐François; Miyake, Yoshihiro; Kim, Dongho; Shinokubo, Hiroshi
Abstract: N‐Alkylation significantly changes the electronic and optical properties, as well as the reactivity of nitrogen‐containing π‐conjugated molecules. In this study, it is found that treating 5, 15‐diazaporphyrins with methyl triflate selectively affords the corresponding N ‐methyl‐5, 15‐diazaporphyrinium cations in good yield. N‐Methylation substantially alters the electronic properties and reactivity of diazaporphyrins. The electron‐accepting properties of the N ‐methyl‐5, 15‐diazaporphyrinium cations are enhanced due to their lowered LUMO level. Stabilization of the LUMO energy enables regio‐ and stereoselective Diels–Alder reactions of the cationic diazaporphyrin with cyclopentadiene. N‐Methylation also enhances the acidity of the inner NH protons, and thus, allows facile deprotonation to provide nitrogen‐substituted isoporphyrin analogues with only one NH group in the central cavity. Abstract : Fine‐tuning reactivity : Treatment of 5, 15‐diazaporphyrins with methyl triflate selectively provides N ‐methyldiazaporphyrinium cations, which exhibit strong electron deficiency and increased reactivity. The former manifests in facile deprotonations to afford a nitrogen‐substituted isoporphyrin analogue. The latter is reflected in highly regio‐ and stereoselective Diels–Alder reactions with cyclopentadiene.